A new species of Microkayla (Anura: Craugastoridae: Holoadeninae) from Department La Paz, Bolivia - de La Riva, Ignacio; Cortez, Claudia; Burrowes, Patricia A. (Zootaxa, 2017)
We describe a new species of direct-developing frog of the genus Microkayla from the Cordillera Real of the Bolivian Andes, in the Department of La Paz. The new species, Microkayla huayna sp. nov., is closely related to M. teqta and can be distinguished from other species of the genus by its brown dorsal skin and the presence of a large dark brown vocal sac in males. This is the second species of Microkayla known from the Zongo Valley, and the ninth in the Cordillera Real, contributing to a total of 22 described species in Bolivia. Given its small distribution range, we recommend to considering it as Vulnerable according to IUCN criteria.